2009
DOI: 10.1002/mop.24321
|View full text |Cite
|
Sign up to set email alerts
|

Resonant properties of the Sierpinski‐based fractal resonator and its application on low‐loss miniaturized dual‐mode bandpass filter

Abstract: the maximum of Ϫ40 dB. S 21 showed a similar shape as S 31 and S 41 , but slightly exceeded Ϫ40 dB in the specific frequency band, 5-7 GHz. It is a reason that only one EBG cell exists between port 1 and 2, so the suppression function of EBG did not operate properly. So, it was confirmed from the results that the proposed triangular EBG structure can provide the means of effectively eliminating SSN at the entire PCB board. CONCLUSIONIn this article, a novel uniplanar compact electromagnetic bandgap (UC-EBG) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…At center frequency ( f 0 ) of 630 MHz, bandwidth of 552–708 MHz (3‐dB fractional bandwidth of 24.8%) and low insertion loss of –1.38 dB are obtained. In contrast to the size reduction of 50% [4], 58% [5], and 24% [12], a 76.4% size reduction is obtained in the proposed filter.…”
Section: Simulation and Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…At center frequency ( f 0 ) of 630 MHz, bandwidth of 552–708 MHz (3‐dB fractional bandwidth of 24.8%) and low insertion loss of –1.38 dB are obtained. In contrast to the size reduction of 50% [4], 58% [5], and 24% [12], a 76.4% size reduction is obtained in the proposed filter.…”
Section: Simulation and Resultsmentioning
confidence: 88%
“…And the patch resonators using inductively loaded crossed‐slots or right crossed‐slots are used to reduce the loss and to generate the BPF with transmission zeroes. Recently, the dual‐mode filters with Sierpinski‐based fractal resonator were introduced [10–12]. The basic characteristics of the fractal geometry are space‐filling and self‐similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, research work in this field has shown a dramatic increase. A variety of fractal geometries have been applied to design compact BPFs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Dual‐mode filters have been widely used in wireless communications systems because of their advantages in applications such as small size and low loss . There are several commonly used dual‐mode patch resonators including crossed slots , loaded crossed‐slots , right crossed‐slots , slot etched , and fractal configurations in a square patch. The arc‐oriented slot etched into a circular patch was used to design a dual‐mode dual‐band BPF .…”
Section: Introductionmentioning
confidence: 99%